Utilizing an electron-deficient thieno[3, 4-c]pyrrole-4, 6-dione (TPD) unit as a π-bridge to improve the photovoltaic performance of A–π–D–π–A type acceptors. Issue 45 (28th October 2020) - Li, Jianfeng; Sun, Chenkai; Tang, Ailing; Zhang, Bao; Guo, Qiang; Zhou, Erjun; Li, Yongfang
Abstract : Thieno[3, 4- c ]pyrrole-4, 6-dione (TPD) was used as a π-bridge to synthesize A–π–D–π–A type NFAs, which realized a PCE of 10.4% by using PTQ10 as the electron donor. Abstract : The control of intramolecular charge transfer between the fused-ring core and terminal unit by selecting a suitable π-bridge has a strong impact on the photovoltaic performance of A–π–D–π–A type non-fullerene acceptors (NFAs). Here, we used a strong electron-deficient unit, thieno[3, 4- c ]pyrrole-4, 6-dione (TPD), as a π-bridge to synthesize a new NFA, TPD8, which exhibited a low optical bandgap of 1.46 eV. Organic solar cells based on PTQ10 :TPD8 gave a power conversion efficiency (PCE) of 10.4% with a relatively high open-circuit voltage ( V OC ) of 0.91 V and low energy loss of 0.55 eV. This work proved that electron-deficient units were also a good choice for the construction of high-performance A–π–D–π–A type NFAs.